Big data : a revolution that will transform how we live, work, and think - Mayer-Schönberger, Viktor (Houghton Mifflin Harcourt, 2013)
Explores the idea of big data, which refers to our newfound ability to crunch vast amounts of information, analyze it instantly, and draw profound and surprising conclusions from it--